Family Guide to the National Insurance Scheme ([London] : His Majesty's Stationery Office, 1948)
1948 1948 1940s 32 pages : illustrations If you are insured under the present National Health Insurance Scheme you will be able to count the contributions paid under that Scheme towards the contributions needed to qualify for payment of Sickness Benefit. If you have already paid 104 contributions under the present Scheme you will be treated as if you had paid 156 under the new Scheme. Similarly your record of contributions paid or credited under the present Scheme before 5th July 1948 will affect your rate of benefit under the new Scheme. 22. How Long may I Draw Sickness Benefit ? Until you have paid 156 Class 1 or Class 2 contributions you cannot get Sickness Benefit for more than 312 days. After drawing it for 312 days you cannot draw the benefit again until you have been back at work for 13 weeks or more. But once you have paid 156 Class 1 or Class 2 contributions, Sickness Benefit is payable, if necessary, until pension age, so long as you are incapable of work because of disease or disablement. 23. Waiting Period. You will not receive benefit for the first three days of sickness unless you are sick or unemployed for 12 days or more during the period of 13 weeks from the first of the three days. These 12 days need not follow one after the other ; any two days may be counted if they are less than a week apart. On a later claim for benefit you will not have to serve a fresh waiting period unless more than 13 weeks have gone by since the end of your last spell of sickness or unemployment. UNEMPLOYMENT BENEFIT 24. What are the Rates of Benefit ? The rates of Unemployment Benefit are the same as the rates for Sickness Benefit 18 345/3/2/10